2018
DOI: 10.1128/mcb.00385-18
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the Endocytic Protein Hip1 Leads to Decreased Gdpd3 Expression, Low Phosphocholine, and Kypholordosis

Abstract: Deficiency of huntingtin-interacting protein 1 (Hip1) results in degenerative phenotypes. Here we generated a deficiency allele where a floxed transcriptional stop cassette and a human cDNA were knocked into intron 1 of the mouse locus.-mediated germ line excision of the stop cassette resulted in expression of HIP1 and rescue of the knockout phenotype.-mediated excision led to HIP1 expression in spleen, kidney and liver, and also rescued the phenotype. In contrast, -mediated, brain-specific HIP1 expression did… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 59 publications
2
6
0
Order By: Relevance
“…3 ). Consistent with a previously reported Gdpd3 -deficient mutant 29 , our Gdpd3 −/− mice were born at the expected Mendelian ratio and appeared healthy (data not shown). Thus, the Gdpd3 - mediated lysophospholipid metabolic pathway is dispensable for normal mouse development and survival.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…3 ). Consistent with a previously reported Gdpd3 -deficient mutant 29 , our Gdpd3 −/− mice were born at the expected Mendelian ratio and appeared healthy (data not shown). Thus, the Gdpd3 - mediated lysophospholipid metabolic pathway is dispensable for normal mouse development and survival.…”
Section: Resultssupporting
confidence: 92%
“…g Survival rates of Gdpd3 +/+ tet-CML-affected mice (18 males, eight females, n = 26 biologically independent samples) and Gdpd3 +/+ tet-CML-affected mice (19 males, four females, n = 23 biologically independent samples) after induction of CML by Dox withdrawal (P-value, Log-rank non-parametric test). a previously reported Gdpd3-deficient mutant 29 , our Gdpd3 −/− mice were born at the expected Mendelian ratio and appeared healthy (data not shown). Thus, the Gdpd3-mediated lysophospholipid metabolic pathway is dispensable for normal mouse development and survival.…”
Section: Resultssupporting
confidence: 70%
“…In this review, I have attempted to put into a broader biological context our recent findings on the role of lysophospholipid metabolism in general, and Gdpd3 in particular, in CML stem cells in vivo. Importantly, healthy Gdpd3-deficient mice show no obvious defects [ 14 , 45 ], suggesting that specific inhibition of Gdpd3-mediated lysophospholipid metabolism may be a viable means of therapeutically targeting CML stem cells without generating harmful side effects in normal tissue stem cells. Future work should determine if lysophospholipid metabolism is critical in other types of hematological cancer stem cells and/or in solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic alterations were rescued by expression of human HIP1 [149] thus proving the specificity of the phenotype. More recently, an interesting HIP1 KO mouse model with the option of conditional re-expression of a single copy of human HIP1 in specific tissues was generated, in order to unravel the tissue-specific function of HIP1 [155]. In contrast to the proposed role of HIP1 as sorter for glutamate receptors in the brain, this mouse model revealed that the selective expression of HIP1 under the brain-specific hGFAP promoter was not sufficient to rescue the presumably neurodegenerative phenotypes observed in HIP1 KO mice, while its expression in spleen, liver and kidney did rescue, thus arguing for an important role of HIP1 in these organs.…”
Section: Lessons From Hip1-and Hip1r-deficient Animal Modelsmentioning
confidence: 99%
“…In contrast to the proposed role of HIP1 as sorter for glutamate receptors in the brain, this mouse model revealed that the selective expression of HIP1 under the brain-specific hGFAP promoter was not sufficient to rescue the presumably neurodegenerative phenotypes observed in HIP1 KO mice, while its expression in spleen, liver and kidney did rescue, thus arguing for an important role of HIP1 in these organs. Interestingly, the DKO mice were also shown to have low phosphocholine levels, however, it is presently enigmatic how this is linked to the phenotypic alterations [155]. Studies involving HIP1 KO mouse models also indicated that loss of HIP1 protects against arthritis, likely due to reduced invasiveness of synovial fibroblasts [156] and that HIP1 deficiency inhibits prostate tumorigenesis in vivo [157].…”
Section: Lessons From Hip1-and Hip1r-deficient Animal Modelsmentioning
confidence: 99%